Adu Kuat Model Pendudukan Tanah Perjanjian oleh Bangsa Israel dalam Perspektif Arkeologi Biblika - Jon, Jon (Basilius Eirene Press, 2025)
The model of the occupation of the promised land has become a topic that is often discussed by theologians with their respective arguments. Therefore, the purpose of this research is to see and find out which model of the occupation of the promised land really fits the biblical facts and historical facts supported by archaeological findings. The research method used is a qualitative method with a biblical archaeological interpretation approach and literature review. The result of this research is that the conquest model is the model of occupation of the promised land that best fits the biblical narrative and is strongly supported by existing archaeological finds. So the model of conquest is undoubtedly the model that Joshua and the Israelites used when they occupied the land of Canaan.